Perbandingan Total Mikroba Kombucha dengan Variasi Jenis Teh dan Lama Fermentasi - Azrini Khaerah; Halijah Halijah; Nurhilmi Nawir (Fakultas MIPA UNM, 2020)
Abstract. Kombucha is a fermented beverage made from tea and sugar. This fermentation is a work of bacteria and yeast consorsia that make a powerful symbiosis cooperation resulting kombucha with quality chemically increased. This kombucha is a healthful beverage for its consumer. Fermentation process can change the tea phisically, such as its taste, colour and flavor. During the fermentation period, the total cell of bacteria and yeast also change. In this research, kombucha is made from 4 different tea, such as black tea, green tea, oolong tea and white tea. As a result, found that the tea as a substrate and also the fermentation period affect the total of colony and cell of bacteria and yeast. In white tea and black tea kombucha perform decreased of total cell bacteria and yeast by the fermentation period, while in green tea and oolong tea kombucha increased. Keywords. kombucha, fermentation, total microbes, SCOBY, haemacytometer